2020
DOI: 10.3389/fonc.2020.00344
|View full text |Cite
|
Sign up to set email alerts
|

NTCP Models for Severe Radiation Induced Dermatitis After IMRT or Proton Therapy for Thoracic Cancer Patients

Abstract: Radiation therapy (RT) of thoracic cancers may cause severe radiation dermatitis (RD), which impacts on the quality of a patient's life. Aim of this study was to analyze the incidence of acute RD and develop normal tissue complication probability (NTCP) models for severe RD in thoracic cancer patients treated with Intensity-Modulated RT (IMRT) or Passive Scattering Proton Therapy (PSPT). We analyzed 166 Non-Small-Cell Lung Cancer (NSCLC) patients prospectively treated at a single institution with IMRT (103 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 54 publications
0
21
0
Order By: Relevance
“…A group of patients was treated for Hodgkin lymphoma (HL) at the University “Federico II” of Napoli (Comitato Etico per le Attività Biomediche, IRB 222-10) with 3D conformal RT (3D-CRT) [ 15 , 16 ]. A second group was treated for locally advanced non-small cell lung cancer (NSCLC) at the University of Texas MD Anderson Cancer Center of Houston (IRB 2008-0133) with image-guided intensity-modulated RT (IMRT), and a third one with passive-scattering proton therapy (PSPT) [ 17 , 18 ]. Lastly, a group of patients was treated for NSCLC at the Memorial Sloan Kettering Cancer Center of New York (IRB #16-142) with stereotactic body RT (SBRT) [ 19 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A group of patients was treated for Hodgkin lymphoma (HL) at the University “Federico II” of Napoli (Comitato Etico per le Attività Biomediche, IRB 222-10) with 3D conformal RT (3D-CRT) [ 15 , 16 ]. A second group was treated for locally advanced non-small cell lung cancer (NSCLC) at the University of Texas MD Anderson Cancer Center of Houston (IRB 2008-0133) with image-guided intensity-modulated RT (IMRT), and a third one with passive-scattering proton therapy (PSPT) [ 17 , 18 ]. Lastly, a group of patients was treated for NSCLC at the Memorial Sloan Kettering Cancer Center of New York (IRB #16-142) with stereotactic body RT (SBRT) [ 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…More details on the protocols and treatment characteristics for each cohort are published elsewhere [ 3 , 13 , 18 , 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…However, more and more evidence suggests that variable RBE calculation should be performed for patients undergoing proton therapy. Some higher-than-expected toxic effects such as brain necrosis [ 34 , 35 ] and skin toxicities [ 36 ] are possibly related to higher-than-expected RBE doses in some anatomic regions. Figure 6 displays dose distributions with constant RBE of 1.1 and variable RBE model in the right brachial plexus region in a patient who developed arm injury after proton treatment in our center.…”
Section: Review Of Robust Optimization Technology To Manage Various Sources Of Uncertaintymentioning
confidence: 99%
“…Finally, an NTCP model has been developed by Palma et al [33] for severe radiation dermatitis based on IMRT and IMPT on NSCLC cohort. Cutaneous toxicity has not been evaluated specifically for HL proton therapy, but Fellin et al [34] found that breast proton therapy could increase skin morbidity compared with IMRT if the skin were not considered as an OAR.…”
Section: Considerations On Other Organs-at-riskmentioning
confidence: 99%